Cytokines: Application in recurrence appraisal for differentiated thyroid carcinoma and their relation with radioiodine ablation. Issue 10 (18th June 2021) - Yang, Mengdie; Yin, Yuzhen; Zhang, Jiajia; Yi, Wanwan; Liu, Jin; Chen, Duo; Zhang, Han; Fan, Xin; Zhang, Yu; Zhu, Mengqin; Qin, Shanshan; Lv, Zhongwei; et al.
Abstract: The limitations in discriminating preablation disease‐active status of differentiated thyroid carcinoma (DTC) still represent a major challenge to radioiodine dose management. Cytokines, the small protein signaling molecules that constitute the thyroid tumor microenvironment, play significant roles in the facilitation of intercellular communication and the control of tumorigenesis. Also, more attention should be paid to the molecular events within the innate and adaptive immune systems that occur after the organism being exposed to ionizing radiation. Therefore, we implemented a study of 260 patients with DTC in thyroid hormone withdrawal status who were treated with total thyroidectomy to explore the relationship between cytokines and recurrence/active disease status. Besides, we made a cross‐sectional study to analyze pre‐ and post‐ablation serum concentration of cytokines of 86 patients with DTC. There was a relationship between clinicohistopathological characteristics of patients with DTC and the presence of cytokines. It is noteworthy that patients with recurrence/active disease were at a higher serum interleukin‐2 receptor (IL‐2R) level than the disease‐free patients (213.59 ± 75.43 pg/ml vs. 186.80 ± 77.40 pg/ml, P = 0.005). Positive correlation was observed between serum IL‐2R and thyroglobulin (Tg) ( P = 0.003). We also found significant changes in the cytokine profile after radioiodine ablation, including the decrease of tumor necrosis factor‐α and IL‐8 ( P < 0.001, P < 0.001, respectively), and increase of IL‐2R ( P < 0.001). Thus, we suggest that serum IL‐2R may assist in evaluating the disease status during the post‐thyroidectomy follow‐up and radioiodine therapy has an immunoregulatory effect on serum cytokines. Abstract : In our research, serum cytokines play significant roles in discriminate differentiated thyroid cancer patients with active disease. Besides, we also found that radioiodine ablation obtains immunoregulatory effects on serum cytokines.